Factors influencing management of agitation in aged care facilities: A qualitative study of staff perceptions. Issue 1 (27th October 2020) - Watson, Karen; Hatcher, Deborah
Abstract: Background: Agitation in older people is commonly associated with cognitive decline, complex medical diagnoses and polypharmacy. Impaired communication and comprehension within a dementia trajectory adds complexity to assessment and management. Despite high prevalence, agitated behaviours remain challenging to manage in residential aged care settings. Aim: To explore staff perceptions of agitation in residents of aged care facilities, including the influence of dementia, when selecting management strategies to reduce agitated behaviour. Design: Qualitative descriptive. Methods: Semi‐structured interviews with 11 aged care staff were conducted at two aged care sites. Transcripts were examined using content analysis to identify common issues and categories. The study complied with COREQ guidelines (see. Appendix S1). Results: Participants reported managing resident agitation at least once per shift; most frequently manifesting as wandering, restlessness or aggression. Management strategies included distraction, providing space, knowing the resident, identifying causative factors, spending individual time and if necessary medication administration. Agitation management was more challenging for residents with dementia due to impaired communication or comprehension of instruction. Conclusions: While participants strived to deliver individualized person‐centred care, this was difficult given time and resource constraints. Contemporary management of agitation therefore remains variable in everyday practice, with resident preference used when causative factors were known. Conversely, for residents with impaired communication and/or comprehension, distraction and chemical restraint were commonly used. Nuanced education for assessment and management is recommended to better address this unmet need for some residents. Relevance to clinical practice: For optimal care, appropriate allocation of time and resources is necessary to identify causative and contextual factors for individual residents. Recommendations are for additional staff training in communication and attitude, and collaborating with frontline staff to develop a practical guide for management of agitation in aged care. These simple initiatives may help to improve consistency of care delivery and resident outcomes.